THE EVOLVING ROLE OF TEACHERS IN BLENDED LEARNING FROM INSTRUCTORS TO FACILITATORS - Shahina Shukhratova (TADQIQOTLAR, 2025)
Abstract The rapid integration of technology in education has transformed the traditional role of teachers, particularly in blended learning environments. This article explores the evolving role of teachers from instructors to facilitators in blended learning settings. By examining key methodological aspects, this study highlights the importance of adaptability, engagement, and collaborative learning. The findings indicate that as teachers transition to facilitators, they enhance student autonomy and foster a more interactive learning environment. This paper provides insights for educators and institutions aiming to optimize blended learning experiences.